INTERNALIZING THE VALUES OF RELIGIOUS MODERATION IN “JEDA NULIS” CHANNEL FOR MILLENIALS - M. Riyan Hidayat (Tatar Pasundan: Jurnal Diklat Keagamaan, 2022)
The bombing of the Makassar Cathedral Church and the shooting at the National Police Headquarters reflects radicalism among the youth. The two perpetrators before carrying out their actions both wrote messages to their families that they were ready to be martyred to carry out jihad as the highest practice in Islam. The internalization of radicalism among millennials through religious propaganda on social media shows the importance of platforms to counter these issues. Therefore, the author makes phenomenological research using the concept of internalization as the formal and material object in form of videos on the "pause writing" channel. In this case, the author uses the descriptive-analytic-critical method through his youtube content about religious moderation. The results show that Habib Hussein Ja'far Al-Hadar has carried out three stages of value internalization consisting of value transformation, value transactions, and trans-internalization. It demonstrates that the YouTube channel's programming is beneficial in combating extremism and educating millennials about religious tolerance.Keywords: moderation; social media; millennials.